Oceanic and atmospheric extremes motivate a new hypothesis for variable marine survival of Fraser River sockeye salmon. (8th May 2014) - McKinnell, Skip; Curchitser, Enrique; Groot, Kees; Kaeriyama, Masahide; Trudel, Marc
Abstract In spite of a relatively optimistic pre‐season forecast, the total return of adult sockeye salmon (Oncorhynchus nerka) to the Fraser River (British Columbia, Canada) in 2009 was the lowest recorded since quantitative records began in the late 1940s. A plausible mechanism is proposed that links a sequence of extreme oceanic and climatic events to poor marine survival. It began with record‐setting snow packs in the coastal mountain range during the winter of 2007 that led to the development of unprecedented oceanographic conditions in the spring of 2007 from Queen Charlotte Strait in central British Columbia to Southeast Alaska. When combined with equally extreme atmospheric anomalies in the region in the spring of 2007, with a winter wind regime persisting through July, a coastal surface ocean with characteristics that are known to be associated with lower marine survival was established. Most of the sockeye salmon that were expected to return to the Fraser River as adults in 2009 passed through this atypical ocean as juveniles on their migration to the open ocean in 2007. A trophic gauntlet hypothesis is proposed as a new paradigm to describe the oceanic environment faced by sockeye salmon after they emigrate northward from the Strait of Georgia. The hypothesis identifies a new type of high nutrient low chlorophyll region that can explain how oceanographic extremes at critical locations along the migration route beyond the Strait of Georgia can reduce marine survival in some years.